Study of Tiu Kulit Dam Reservoir Operational Pattern Simulation in Sumbawa Island - Putranto, Yoyok Dwi; Harisuseno, Donny; Prayogo, Tri Budi (Civil and Environmental Science Journal (CIVENSE), 2023)
Tiu Kulit Reservoir plays a pivotal role in managing water resources in West Nusa Tenggara, Indonesia, serving as a vital source for raw water, irrigation, and livestock consumption in the neighboring regions. This study aims to assess the operational dynamics of Tiu Kulit Reservoir across varying hydrological conditions, namely dry, normal, and wet years. The analysis is based on inflow rates and equilibrium water surface elevations. To achieve the objectives, an investigation of the reservoir's operation pattern was conducted. Inflow rates and equilibrium water surface elevations were scrutinized to discern operational behaviors under different hydrological scenarios. The findings indicate distinct operational strategies for Tiu Kulit Reservoir. During dry years, the outflow rate is restricted to 1.20 m3/s at a water surface elevation of +53.07 m. Conversely, the reservoir's operation in normal and wet years allows for a maximum outflow rate aimed at satisfying water demand, set at +57.00 m. In instances of excessive rainfall, the study highlights the potential for overflow beyond the spillway threshold. The study underscores the significance of these results for effective water management and resource allocation in the region. Understanding the reservoir's behavior under various conditions enables informed decision-making and sustainable utilization of water resources. To build upon this study, it is recommended to implement continuous monitoring systems for both inflow and outflow rates. Furthermore, the installation of rainfall monitoring stations within the catchment area would enhance data accuracy. Regular evaluations of the reservoir's operational patterns are also advised, allowing for adaptive strategies in response to evolving climate conditions. Moreover, future research endeavors should focus on augmenting water supply to meet the demands of a growing population and livestock, while optimizing agricultural practices to boost productivity.